Extinción de medidas cautelares y afectación a su naturaleza provisional:artìculo 625 del código procesal civil peruano - Reyes Espejo, Claudia Beatriz (2019)
The purpose of the present investigation was to analyze how the extinction of precautionary expected in the article 625 of the Peruvian Civil Procedure Code affects its provisional nature, by virtue of this problem, topics such as: The guardianship were developed in the theoretical framework effective jurisdictional; precautionary measures, and within this section are the budgets, purpose, characteristics, types, concurrence, effectiveness, extinction and lifting; also the general notions of the prescription and expiration; also, Registration Law, whose content includes its definition, characteristics, elements, function, principles, basic notions of Public Registries and Registry Court and the analysis carried out regarding the regulation of the extinction of precautionary measures in the Peruvian legal system and in the Comparative law. In addition, the deductive-inductive, hermeneutic-juridical methods were applied, as well as the techniques of documentary collection, of the normative interpretation, of signing, analysis or study of cases, doctrinal, jurisprudential and code documents; methods and techniques that influenced the analysis of the position of the doctrine on article 625, comparative legislation, resolutions, pronouncements and plenary sessions issued by the Court Registry, even concluding that the regulation on the extinction of precautionary measures in the Peruvian Civil Procedure Code , affects its provisional nature for two fundamental reasons: The first, because it prevents its expiration and thereby limits the speed of the proceedings, constituting an inequality between the parties, violating the principle of reasonableness of the jurisdictional operator and rendering obsolete the legal concept of the updating, which acts as a remedy to the negligent action of the applicant; and the second because it affects the performance of Public Registries, rejecting the requests presented before the offices of Public Registries, given that this entity supports the current regulations of our adjective code, in application of the principle of legality, legitimacy and formality.